DIGITAL COMMUNICATION AS A STRATEGY FOR THE POSITIONING OF THE BRAND BALANCED EXIBAL - Isín Vilema, Manuel David; Largo Naula, Nancy Cristina; Ramos Jiménez, Rosa Belén; Rodríguez Galán, Andrés Leandro (mktDESCUBRE, 2020)
Digital Communication became a valuable tool as a brand positioning strategy, allowing us to effectively communicate content that attracts the attention of potential clients, using current digital platforms. This research aims to determine the influence of digital communication on the positioning of the EXIBAL balanced brand, has a mixed approach, as analytical, ethnographic and descriptive methods of study were used, the type of research is quasi-experimental and the sample There are 157 clients under study, as data collection techniques, surveys, interviews and observation have been used, for the development internal information was collected on the products that EXIBAL sells, as well as external information to identify the current situation of social networks used by the organization and identify the perception of customers regarding the brand, with the data obtained a media plan and positioning strategies in digital media were designed. The results showed deficiencies in the content published in digital media and its influence on brand positioning, as a starting point the company logo was redesigned as the basis for the creation of digital strategies generating experiences of the product with the client.